2017
DOI: 10.1002/mp.12018
|View full text |Cite
|
Sign up to set email alerts
|

A portal dosimetry dose prediction method based on collapsed cone algorithm using the clinical beam model

Abstract: The method developed here can be easily implemented into clinic, as neither additional modeling of the clinical energy nor an independent image prediction algorithm are necessary. The main advantage of this method is that portal dose prediction is calculated with the same algorithm and beam model used for patient dose distribution calculation. This method was independently validated with an ionization chamber matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Gamma pass rates (3%, 3 mm DTA) of >94% were achieved for IMRT and VMAT fields applied to inhomogeneous and anthropomorphic phantoms. Martinez-Ortega et al [22] used Pinnacle (v8.0m) and introduced a water-equivalent virtual EPID model to the TPS but also implemented a photon spectral correction based on radiological thickness of the patient along individual raylines. They compared predictions to a-Si EPID measurements that were converted to be water-equivalent, and achieved gamma pass rates (5%, 3 mm DTA) of >80.3% for three square fields on an anthropomorphic phantom (cranial, thorax, and pelvis sites) and >94.6% for five IMRT fields on the pelvis site.…”
Section: Predictive Methods or Algorithmsmentioning
confidence: 99%
“…Gamma pass rates (3%, 3 mm DTA) of >94% were achieved for IMRT and VMAT fields applied to inhomogeneous and anthropomorphic phantoms. Martinez-Ortega et al [22] used Pinnacle (v8.0m) and introduced a water-equivalent virtual EPID model to the TPS but also implemented a photon spectral correction based on radiological thickness of the patient along individual raylines. They compared predictions to a-Si EPID measurements that were converted to be water-equivalent, and achieved gamma pass rates (5%, 3 mm DTA) of >80.3% for three square fields on an anthropomorphic phantom (cranial, thorax, and pelvis sites) and >94.6% for five IMRT fields on the pelvis site.…”
Section: Predictive Methods or Algorithmsmentioning
confidence: 99%
“…Currently, amorphous silicon electronic portal imaging devices (a-Si EPIDs), which have high spatial resolutions, large twodimensional arrays, and approximately linear dose responses (11)(12)(13), are commonly used in clinical in vivo dosimetry (14)(15)(16)(17)(18). Although gamma pass rate threshold-based EPID in vivo dosimetry can be used to monitor treatment through single pass rate values (16)(17)(18)(19), research on EPID dosimetry by Hsieh Emmelyn S et al (20) has revealed that, under 3%/3 mm and 95% pass rate threshold criteria, position errors greater than 2 cm can be detected, which is unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…This method is widely used in clinics, but may not reflect the errors introduced in the TPS calculation process. Second, the EPID image is converted into a dose value and compared with an independent verification system [6,[11][12][13]. Many studies have shown that EPID has the potential to be used as a direct dosimetry tool [14][15][16][17][18] and to detect patient related errors during radiotherapy [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…When some of Varian's EPID are exploited for dose measurement, two factors may affect the dosimetric properties of EPID. One factor is that EPID is mounted on the linac by means of a support arm, and the low-energy scatter ray produced by the interaction between X-rays and the support arm may lead to asymmetry of the EPID image in the inline direction [13,[21][22][23][24][25]; relevant studies show that the effect may exceed 5% [26,27]. The other factor is that EPID requires dark field and flood field calibration to ensure that the response of each pixel is constant, which results in the off-axis response of EPID being different from the actual output of the linac [28,29].…”
Section: Introductionmentioning
confidence: 99%